Modulating the microscopic lattice distortions through the Al-rich layers for boosting the ferroelectricity in Al:HfO2 nanofilms. (10th November 2022) - Yao, Lulu; Das, Sambit; Liu, Xin; Wu, Kai; Cheng, Yonghong; Gavini, Vikram; Xiao, Bing
Abstract: Combining the experimental characterization with the large-scale density functional theory calculations based on finite-element discretization (DFT-FE), we address the stabilization of polar orthorhombic phases (o-HfO2 ) in Al:HfO2 nanofilms by means of the atomic registry distortions and lattice deformation caused by Al substitutional defects (AlHf ) and Schottky defects (2AlHf + VO ) in tetragonal phases (t-HfO2 ) or monoclinic phases (m-HfO2 ). The phase transformation directly from the t-HfO2 into polar o-HfO2 are also elucidated within a heterogeneous distribution of Al dopants in both t-HfO2 bulk crystal structure and Al:HfO2 nanofilm. It is revealed using large-scale DFT calculations that the Al substitutional defects (AlHf ) or the Schottky defect (2AlHf + VO ) could induce the highly extended atomic registry distortions or lattice deformation in the t- and m-HfO2 phases, but such effects are greatly diminished in ferroelectric orthorhombic phase. By purposely engineering the multiple AlHf defects to form dopant-rich layers in paraelectric t-HfO2 nanofilm or bulk crystal, the induced extended lattice distortions surrounding the defect sites exhibit the shearing-like atomic displacement vector field. The large-scale DFT calculations further predicted that the shearing-like microscopic lattice distortions could directly induce the phase transformation from the t-HfO2 into polar orthorhombic phase in both Al:HfO2 bulk crystal and nanofilms, leading to the large remanent polarization observed in Al:HfO2 nanofilms with the presence of Al-rich layers. The current study demonstrates that the ferroelectricity of HfO2 bulk crystal or thin film can be optimized and tuned by delicately engineering both the distribution and concentration of Al dopants in atomic layer deposition without applying the top capping electrode, providing the extra flexibility for designing the HfO2 based electronic devices in the future.